Agroecology and resilience of smallholder food security: a systematic review - Dagunga, Gilbert; Ayamga, Michael; Laube, Wolfram; Ansah, Isaac Gershon Kodwo; Kornher, Lukas; Kotu, Bekele Hundie (Frontiers in Sustainable Food Systems, 2023)
Multiple covariate shocks such as the covid-19 pandemic, the Russia-Ukraine conflict and preexisting climate shocks pose serious threats to smallholder livelihoods. The cascading effects of these multiple shocks, including rising prices of fertilizers and food imports, have rekindled interest in the call for a policy shift towards agroecology. Agroecology in this study is defined as a set of practices based on ecological principles of diversity, synergy and nutrient cycling of agroecosystems, which are capable of enhancing the resilience of smallholder food security while providing ecosystem services. Proponents of the agroecology paradigm argue that it is more sustainable and resilience-enhancing. Yet, the nexus between agroecology, resilience and food security is less understood in the literature. Therefore, this paper aimed at reviewing the existing literature to examine how agroecology could enhance resilience and food security of smallholders.A systematic literature search was performed in Web of Science, Scopus and PubMed based on three keywords, viz; agroecology, resilience and food security. Following the 2020 PRISMA (Preferred Reporting Items on Systematic Review and Meta-Analysis) guideline for systematic literature review, 47 articles were retained for the final review. The results provide empirical evidence that support the potential of agroecological practices in enhancing the resilience and food security of smallholders. The study proposes a framework that links agroecology, resilience and food security, showing the interplay between all three dimensions of agroecology -the science, policy and practices -relevant for successful agroecological transitioning or transformation while identifying gaps for further research.